Hukum Islam Dalam Tata Hukum Indonesia - Pahutar, Agus Anwar; Yunaldi, Wendra; Karim, Shofwan; Am, Rusydi; Wahyuni, Sri (Syekh Ali Hasan Ahmad Addary State Islamic University, 2024)
This study discusses the position and role of Islamic law in Indonesia's national legal system, a pluralistic legal system. As a country with a majority Muslim population, Islamic law has played a significant role, especially in the fields of family law, sharia economics, and waqf. However, the application of Islamic law faces challenges such as legal pluralism, differences in interpretation, social modernization, and commitment to human rights standards. The main issues formulated in this study are how Islamic law is accommodated in the Indonesian legal system, what challenges it faces, and what opportunities can be utilized for its development. The research method used is qualitative descriptive with historical, normative, and sociological approaches. Data is collected through the analysis of documents, such as laws and regulations related to Islamic law, as well as literature studies involving books, journal articles, and policy reports. Data analysis was carried out qualitatively by identifying key themes related to the roles, challenges, and opportunities of Islamic law. The results of the study show that Islamic law has been accommodated in the national legal system through various regulations, such as the Marriage Law, the Sharia Banking Law, and the Zakat Law. The main challenges of its implementation include the gap between regulation and implementation, the pressure of modernization, and the plurality of Indonesian society. On the other hand, the opportunity for the development of Islamic law is quite large, supported by the growth of the sharia economy, technological innovation, and the support of the Muslim community. This study concludes that Islamic law has great potential to develop further as an integral part of Indonesia's legal system, as long as its application is carried out in an inclusive and adaptive manner to the needs of diverse societies.